2002
DOI: 10.1128/jvi.76.7.3374-3381.2002
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Rabies Virus Glycoprotein Results in Enhancement of Apoptosis and Antiviral Immune Response

Abstract: A recombinant rabies virus (RV) carrying two identical glycoprotein (G) genes (SPBNGA-GA) was constructed and used to determine the effect of RV G overexpression on cell viability and immunity. Immunoprecipitation analysis and flow cytometry showed that tissue culture cells infected with SPBNGA-GA produced, on average, twice as much RV G as cells infected with RV carrying only a single RV G gene (SPBNGA). The overexpression of RV G in SPBNGA-GA-infected NA cells was paralleled by a significant increase in casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
172
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 30 publications
(23 reference statements)
17
172
0
6
Order By: Relevance
“…This finding demonstrates that rabies VNA titers, while roughly correlated with protection, are not an absolute indicator of survival against rabies virus challenge. Furthermore, the increased efficacy of the SPBNGAS-GAS vaccine over the SPBNGAS vaccine is consistent with previous studies, suggesting the induction of superior rabies VNA from recombinant rabies viruses expressing two copies of the glycoprotein compared to viruses containing only one copy [16].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This finding demonstrates that rabies VNA titers, while roughly correlated with protection, are not an absolute indicator of survival against rabies virus challenge. Furthermore, the increased efficacy of the SPBNGAS-GAS vaccine over the SPBNGAS vaccine is consistent with previous studies, suggesting the induction of superior rabies VNA from recombinant rabies viruses expressing two copies of the glycoprotein compared to viruses containing only one copy [16].…”
Section: Discussionsupporting
confidence: 78%
“…The SPBNGAS-GAS, which contains an extra copy of the rabies virus glycoprotein gene from SPBN-GAS, was constructed similarly as previously described [16]. The V-RG vaccine (Raboral V-RG ® , Rhone Merieux, Inc., Athens, GA, USA) was obtained from a commercial source.…”
Section: Vaccinesmentioning
confidence: 99%
“…MOKV plus RABV and WCBV plus RABV G protein genes, elicited specific VNAb responses that were comparable to those elicited by the single antigen expressing vaccines and each of the vaccines offered dual protection against challenges with either viruses. Previously, a recombinant RABV which express the RABV glycoprotein gene in duplicate, were found to concomitantly produce more glycoprotein and consequentially elevated neutralizing responses in a back-titration study, as opposed to a RABV expressing only one RABV glycoprotein gene [42]. This observation was supported by survival studies in a mouse model.…”
Section: Discussionsupporting
confidence: 57%
“…However, neither caspase-1 nor caspase-2 activity was detected during the early phase of infection. Lyssavirus-mediated cell death involves an interaction between TRAIL receptors and TRAIL, as demonstrated by experiments using neutralizing antibodies and soluble decoy TRAIL-R1/R2 receptors and is not due to a direct interaction between DR and an external viral protein (i.e., glycoprotein) (22,59). We also demonstrated that the decapsidation and replication of lyssavirus are essential for inducing apoptosis, as supported by UV inactivation, CHX treatment, and the use of BAF to inhibit endosomal acidification.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest for the first time that lyssavirus M proteins are involved in the induction of apoptosis in neuronal cells. This indicates that the viral induction of apoptosis is probably multigenic and not only related to the viral glycoprotein (22,59). M is a small (202-amino-acid), multifunctional protein (25 kDa) that is responsible for the assembly and budding of virus particles (29,30,50) as well as for the regulation of the balance of virus transcription and replication (24).…”
mentioning
confidence: 99%